1980
DOI: 10.1021/jm00181a013
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoaminobenzophenones, a novel class of ring-opened derivatives of 1,4-benzodiazepines

Abstract: A series of noval peptidoaminobenzophenones has been prepared via several routes and was evaluated for CNS activity. The structure--activity relationships in the series are discussed. In general, dipeptido-N-methylaminobenzophenones showed higher activities than the corresponding NH derivatives. Some compounds had very high activities in antipentylenetetrazole and antifighting tests in mice when orally administered. Very weak toxicity was also found in these compounds. Water solubility of the peptidoaminobenzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…2-Aminobenzophenone and its derivatives are important because of their applications in heterocyclic synthesis and medicines (Walsh, 1980). 2-Aminobenzophenone has been used as the starting material for the synthesis of 1,4-benzodiazepines (Sternbach et al, 1962) and antiinflammatory agents (Ottosen et al, 2003) as well as peptidoaminobenzophenones, a class of open-ring derivatives of 1,4-benzodiazepines (Hirai et al, 1980). 2-Aminobenzophenone derivatives have also been used as antimitotic agents (Liou et al, 2002).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…2-Aminobenzophenone and its derivatives are important because of their applications in heterocyclic synthesis and medicines (Walsh, 1980). 2-Aminobenzophenone has been used as the starting material for the synthesis of 1,4-benzodiazepines (Sternbach et al, 1962) and antiinflammatory agents (Ottosen et al, 2003) as well as peptidoaminobenzophenones, a class of open-ring derivatives of 1,4-benzodiazepines (Hirai et al, 1980). 2-Aminobenzophenone derivatives have also been used as antimitotic agents (Liou et al, 2002).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…in vitro, these compounds are stable, and their in vivo hydrolysis by peptidases leads to the release of a benzodiazepine precursor, which then spontaneously cyclises to yield the active drug (Scheme 1). [20][21][22] How-A C H T U N G T R E N N U N G ever, these compounds lack selectivity for cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Dipeptidoaminobenzophenones (1) display sedative, muscle relaxant, and anticonvulsant activities, in particular against metrazol-induced seizures [Hirai et al, 1980;Williams, 1983]. In earlier studies, we reported 3alkoxycarbonylaminomethylcarbonylamino-4-benzoylpyridines (4) [Fiakpui et al, 1990], 1,3-dihydro-5-phenyl-2H-pyrido [3,4-e][1,4]diazepin-2-ones (5) [Fiakpui et al, 1993b], 3-alkoxycarbonylaminomethylcarbonylamino-2-benzoylpyridines (6), and 1,3dihydro-5-phenyl-2H-pyrido[3,2-e][1,4]diazepin-2ones (7) [Fiakpui et al, 1993a] that exhibited anticon-vulsant activities in the subcutaneous metrazol (Met) and maximal electroshock (MES) screens.…”
Section: Introductionmentioning
confidence: 99%